(untitled) (Economics and region, 2020)
The analysis of scientific literature made it possible to systematize modern approaches to the interpretation of the category of «enterprise risk resistance». Thus, the article provides a comparative analysis of the categories «risk», «resistance», «enterprise risk resistance», identifies their common features and differences, and proposes a three-level model of enterprise security. Since the level of enterprise resistance to risk is determined by the level of stability for each component, it is proposed to determine the integral riskiness indicator as the weighted average value of indicators characterizing the current, tactical and strategic level of enterprise resistance to risk.